2019
DOI: 10.5539/gjhs.v11n7p80
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health and Lifestyle/Food Habits in Japanese Junior High School Students

Abstract: Adolescence is a crucial period for health status formation. Adolescence is the period during which health-related behaviours, such as nutrition-related behaviours and physical activities, are developed. Self-rated health (SRH) assessment during adolescence is strongly associated with general well-being and psychosomatic symptoms. The current study investigated the relationship between SRH and lifestyle, eating habits and attitudes toward food among junior high school students. A total of 438 students aged 13&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Third, the results of our previous study of high school students suggested significant associations between SRH and the frequency of eating breakfast and liking home meals, with the results including eating behaviour (Osera et al, 2017). In addition, our previous study of junior high school students suggested that SRH was significantly associated with going to bed early, having good exercise habits, not experiencing headaches and liking home meals (Osera et al, 2019). These results included eating behavior and lifestyle, but the results suggested that SRH may be more closely associated with concern than with actual behaviour.…”
Section: Discussionmentioning
confidence: 84%
“…Third, the results of our previous study of high school students suggested significant associations between SRH and the frequency of eating breakfast and liking home meals, with the results including eating behaviour (Osera et al, 2017). In addition, our previous study of junior high school students suggested that SRH was significantly associated with going to bed early, having good exercise habits, not experiencing headaches and liking home meals (Osera et al, 2019). These results included eating behavior and lifestyle, but the results suggested that SRH may be more closely associated with concern than with actual behaviour.…”
Section: Discussionmentioning
confidence: 84%